Temporal Trends in Online Search Interest in Dental Implant Treatment in Türkiye: A Google Trends–Based Infodemiology Study - Saim Yanık; Mehmet Emrah Polat; Şeğmus Özdemir (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
ABSTRACT Objective: This study evaluated long-term trends in online search interest in dental implant treatment in Türkiye, level and slope changes around March 2020, and associations with year-on-year Consumer Price Index (CPI) change rates. Methods: Monthly relative search volume (RSV) data for five implant-related terms were obtained from Google Trends. Data from 2004–2025 were used for visual assessment and 2014–2025 for inference. Trends were evaluated using linear regression with Newey–West heteroskedasticity- and autocorrelation-consistent (HAC) standard errors and the Mann–Kendall test. Changes around March 2020 were examined using segmented regression. CPI–RSV associations were assessed using Spearman and time-adjusted partial Spearman correlations with Benjamini–Hochberg false discovery rate (FDR) correction. Results: All terms showed significant positive trends during 2014–2025 (all HAC p < 0.001); “implant diş” had the highest mean RSV and largest increase. Most terms showed no significant immediate level or slope changes. “Diş implantı” showed an immediate level decrease (β₂=−1.366; p < 0.001) followed by a positive slope change (β₃=0.0256; p < 0.001), whereas “implant fiyat” showed a negative slope change (β₃=−0.0474; p=0.028). Positive unadjusted CPI–RSV associations weakened after time adjustment; only “implant diş” remained significant after FDR correction (ρ=0.335; q < 0.001). Conclusion: Online search interest in dental implant treatment increased during 2014–2025, with patterns varying by terminology. Heterogeneous changes around March 2020 and attenuation of CPI associations after time adjustment underscore the importance of accounting for secular trends when interpreting online search behavior.